1999
DOI: 10.1105/tpc.11.3.377
|View full text |Cite
|
Sign up to set email alerts
|

LeProT1, a Transporter for Proline, Glycine Betaine, and γ-Amino Butyric Acid in Tomato Pollen

Abstract: During maturation, pollen undergoes a period of dehydration accompanied by the accumulation of compatible solutes. Solute import across the pollen plasma membrane, which occurs via proteinaceous transporters, is required to support pollen development and also for subsequent germination and pollen tube growth. Analysis of the free amino acid composition of various tissues in tomato revealed that the proline content in flowers was 60 times higher than in any other organ analyzed. Within the floral organs, prolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
204
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 181 publications
(210 citation statements)
references
References 44 publications
5
204
0
1
Order By: Relevance
“…This strain carries mutations in the general amino acid (gap1), Pro (put4), and the GABA (uga4) permeases and thus is unable to grow on citrulline, Pro, or GABA as the sole nitrogen source. As controls, strain 22574d was transformed with the expression vector pDR195, with pDR195 harboring the cDNAs of AtProT1, AtProT2, LeProT1, or the amino acid permease AtAAP2 (Kwart et al, 1993;Schwacke et al, 1999). Growth under selective conditions showed that, like AtProT1 and AtProT2, AtProT3 was able to mediate growth on Pro and GABA, but not on citrulline ( Fig.…”
Section: Atprot3 Mediates Growth Of a Pro And Gaba Transport-deficienmentioning
confidence: 99%
See 1 more Smart Citation
“…This strain carries mutations in the general amino acid (gap1), Pro (put4), and the GABA (uga4) permeases and thus is unable to grow on citrulline, Pro, or GABA as the sole nitrogen source. As controls, strain 22574d was transformed with the expression vector pDR195, with pDR195 harboring the cDNAs of AtProT1, AtProT2, LeProT1, or the amino acid permease AtAAP2 (Kwart et al, 1993;Schwacke et al, 1999). Growth under selective conditions showed that, like AtProT1 and AtProT2, AtProT3 was able to mediate growth on Pro and GABA, but not on citrulline ( Fig.…”
Section: Atprot3 Mediates Growth Of a Pro And Gaba Transport-deficienmentioning
confidence: 99%
“…In the last few years, genes encoding transporters for the compatible solutes Pro and Gly betaine were isolated from a number of plant species, including Arabidopsis (AtProT1 and AtProT2; Rentsch et al, 1996), tomato (Lycopersicon esculentum; LeProT1-3; Schwacke et al, 1999), rice (Oryza sativa; OsProT; Igarashi et al, 2000), barley (Hordeum vulgare; HvProT; Ueda et al, 2001), orach (Atriplex hortensis; AhProT1; accession no. AAF76897), and mangrove (Avicennia marina; AmT1-3; Waditee et al, 2002).…”
mentioning
confidence: 99%
“…RNA was isolated from different organs of greenhouse-grown tomatoes (L. esculentum cv Moneymaker) according to the method of Schwacke et al (1999). Reverse transcription was performed with the MAXIscript SP6/T7 in vitro Transcription Kit (Ambion Inc., Austin, TX), using ␣-32 P-UTP.…”
Section: Rna Isolation and Rnase Protection Analysismentioning
confidence: 99%
“…RNA was isolated from different organs of greenhouse grown L. esculentum Moneymaker, as described (Schwacke et al, 1999). RNA gel blots were hybridized in 50% formamide at 42ЊC and washed with 0.2 ϫ SSC/0.1% SDS at 65ЊC (1 ϫ SSC is 0.15 M NaCl and 0.015 M sodium citrate).…”
Section: Lesut Genes and Expression Analysismentioning
confidence: 99%